Compositional adaptability in NPM1-SURF6 scaffolding networks enabled by dynamic switching of phase separation mechanisms - Mylene C. Ferrolino (Nature Portfolio, 2018)
The nucleolus is a membrane-less organelle and both Nucleophosmin (NPM1) and Surfeit locus protein 6 (SURF6) are abundant proteins within the nucleolus. Here the authors employ biophysical methods to study the properties of NPM1-S6N droplets and provide insights into the role of SURF6 in maintaining and modulating the liquid-like structure of the nucleolus.